Typing of emm77 Streptococcus pyogenes strains isolated from different clinical samples - Claudio Palmieri; Maria Stella Princivalli; Lucilla Baldassarri; Roberta Creti; Pietro Emanuele Varaldo; Bruna Facinelli (Microbiologia Medica, 2008)
Population structure analysis of emm77 Streptococcus pyogenes isolates demonstrated that the Clonal Complex ST63/369, previously reported in Italian pharyngeal strains, can also be found in non-pharyngeal strains.The success of ST63/369 may be due to the association of specific resistance [iMLS-B/erm(A); tet(O)] and virulence [internalization-gene prtF1] traits.